Digital Reading Practices and Urban Narratives: Exploring Medan’s Cityscape in Contemporary Literature - Maulina, Intan; Fithriani, Rahmah; Pardi, Pardi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates how Medan’s urban identity is constructed and reimagined through both traditional literary works and digital reading practices. Grounded in the constructivist–interpretive paradigm, it analyzes texts by Titan Sadewo, Ika Natassa, Hasan Al Banna, and Lucya Chriz, along with digital platforms such as @beyondthepage.mdn and KleioBuku. The findings reveal that Medan’s cityscape is a dynamic cultural construct shaped by memory, modernity, and digital participation. Digital literary communities foster new modes of interaction, where readers and writers collaboratively reinterpret urban experiences beyond the printed page. By examining these intersections, the study expands Indonesian urban literary discourse and highlights the transformative role of digital media in shaping contemporary representations of place and identity.